Le « brouilloscope », un nuancier pour éclairer les troubles de la perception - Helma Korzybska (Ateliers d'Anthropologie)
In this contribution, I present the “bluroscope”, a research tool I developed with illustrator Marianne Tricot in the context of my work on the perceptual learning of people who have lost their sight or hearing, and have been respectively fit with retinal and cochlear implants. Within my methodological area of interest with regard to the study of ineffable experiences, the aim of this collaboration was to employ a graphical interpretation of sound and vision descriptions offered by people encountered in the field, in order to better understand the sensory transformations that sustain them. This article looks back at the process of developing that object, starting with the sensory narratives of patients encountered in implantation centres, to show the reflection carried out on graphical interpretation in order to indicate various sensory characteristics and processes (aural and visual). This research, conducted simultaneously with analysis of field data, enabled a better understanding of the nature of changes in the learning of bionic vision and hearing, whose protean appearance proves to be fundamentally attentional.